2013
DOI: 10.1155/2013/408460
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Pelvic Radiotherapy in Patients with Stage II/III Rectal Cancer

Abstract: High-level evidence supports adjuvant radiotherapy for rectal cancer. We examined the influence of sociodemographic factors on patterns of adjuvant radiotherapy for resected Stage II/III rectal cancer. Methods. Patients undergoing surgical resection for stage II/III rectal cancer were identified in SEER registry. Results. A total of 21,683 patients were identified. Majority of patients were male (58.8%), white (83%), and with stage III (54.9%) and received radiotherapy (66%). On univariate analysis, male gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Aside from histologic subtype and older age, we found no other predictors for omission of radiation therapy. Multiple previous studies have demonstrated that new practice guidelines often take more than a decade to be integrated into clinical practice . Similar to our findings, Bagaria found that 60% of patients with Stages II and III sarcomas fail to receive recommended adjuvant radiotherapy .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Aside from histologic subtype and older age, we found no other predictors for omission of radiation therapy. Multiple previous studies have demonstrated that new practice guidelines often take more than a decade to be integrated into clinical practice . Similar to our findings, Bagaria found that 60% of patients with Stages II and III sarcomas fail to receive recommended adjuvant radiotherapy .…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our findings, Bagaria found that 60% of patients with Stages II and III sarcomas fail to receive recommended adjuvant radiotherapy . Lack of adoption of evidence‐based guidelines has also been noted for multiple other malignancies including rectal and colon cancer , but the reason for such practices are unclear. Other factors identified in the SEER registry that contribute to under treatment include lower socioeconomic status, race, and location (urban vs. rural) .…”
Section: Discussionsupporting
confidence: 85%
“…Similar RT underuse among patients in the SEER registry with 32.35% of stage II/III rectal cancer patients not receiving RT was reported. 2 Based on guidelines and expert opinion, the optimal utilization rate was estimated around 73.6% (±0.7%) 25 ; however, the actual utilization rate was found lower. 26, 27 Similar to previous studies, 2, 27, 28 our study found that patients with older age, female sex and a diagnosis in earlier study years were associated with a decreased likelihood of receiving RT.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic magnetic resonance imaging (MRI) is routinely used to determine the use of preoperative and postoperative radiotherapy in management, further increasing the complexity of decision making. International evidence suggests there is significant variation in the use of radiotherapy in the management of rectal cancer [16] , [17] , [18] , [19] , [20] , but, unlike the UK, many countries do not routinely use MRI for pelvic staging, which may explain in part the variation observed. Little is known about the patterns of radiotherapy use in England.…”
Section: Introductionmentioning
confidence: 99%